Compatibility of the English Needs of Automation and Office Governance Majors Students to The 2013 English Curriculum - Lina Puspita Dewi; Dwi Rukmini; Udi Samanhudi; Arif Susanto (Journal of Vocational Education Studies, 2022)
English teaching in Vocational High School can be taken into account as English for Specific Purposes (ESP) since vocational education aims to prepare students to be a professional in the specific field of work. ESP is designed according to the needs and purposes of the learners in learning the targeted-language. This paper aims to check whether the latest 2013 English curriculum has met the vocational high school students’ needs or not. This study was done in a public vocational high school in Blora regency, Central Java. The data was collected by using observation checklist, questionnaires, and study document. The observation was done to investigate the practice of the 2013 English curriculum in the Automation and Office Governance Major. The questionnaires were given to the students, graduates, and users of graduates to analysis the English needs. Study documents were used to confirm whether the practice and documents prepared by the English teacher is suitable with the curriculum or not.